Thermal epimerization of inositol 1,3-benzylidene acetals in the molten state - Gurale, Bharat P.; Krishnaswamy, Shobhana; Vanka, Kumar; Shashidhar, Mysore S. (Tetrahedron, 2011)
1,3-O-Benzylidene-2,4,5,6-tetra-O-substituted-myo-inositol derivatives obtained by the DIBAL-H reduction of the corresponding myo-inositol 1,3,5-orthobenzoate derivatives undergo epimerization at the acetal carbon on heating, in the molten state, just above their melting point. The same epimerization reaction does not proceed either in the crystalline state or in solution. DFT calculations suggest that the epimeric acetal obtained by this thermal process is relatively more stable than the starting acetal. Either of these acetals could not be obtained by the reaction of the corresponding inositol derived diol with benzaldehyde. These observations constitute a novel reaction solely in the molten state, which are rarely encountered in the literature. X-ray crystal structures of the epimeric acetals as well as their radical deoxygenation reaction are also reported. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: cyclitols; Deoxygenation; Epimerization; Melt; Xanthate

Radical mediated deoxygenation of inositol benzylidene acetals: conformational analysis, DFT calculations, and mechanism - Gurale, Bharat P.; Vanka, Kumar; Shashidhar, Mysore S. (Carbohydrate Research, 2012)
Xanthates of 1,3-benzylidene acetal derivatives of myo- and neo-inositols undergo dideoxygenation under Barton-McCombie conditions, as a result of intramolecular abstraction of the benzylidene acetal hydrogen and subsequent cleavage of the acetal ring. Scrutiny of structure of these bicyclic inositol derivatives shows that although the conformation of the two rings can vary depending on the configuration of the inositol ring and the phase in which the molecules are present, both the xanthates lead to the formation of the same dideoxyinositol. DFT calculations on these molecular systems suggest that neo-inositol derivatives undergo conformational change prior to radical formation while myo- inositol derivatives undergo conformational change subsequent to radical formation, during the deoxygenation reaction. A low barrier for intramolecular hydrogen transfer supports the extreme facility of this deoxygenation reaction. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Deoxygenation; DFT; Inositol; Mechanism; Radical; Xanthate